POSTINJECTION CONTRACTURE OF THE MANDIBLE (Spectrum Journal of Innovation, Reforms and Development, 2022)
The relevance of the topic. Local anesthesia in dentistry can currently be considered as a separate discipline of dentistry. As experience shows, anesthesia has been and remains one of the most important problems, both in general dentistry and in its private sections.